2010
DOI: 10.1093/humupd/dmq052
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics and the placenta

Abstract: Studies in both animals and humans have made it increasingly clear that proper epigenetic regulation of both imprinted and non-imprinted genes is important in placental development. Its disturbance, which can be caused by various environmental factors, can lead to abnormal placental development and function with possible consequences for maternal morbidity, fetal development and disease susceptibility in later life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
235
0
9

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 330 publications
(248 citation statements)
references
References 201 publications
4
235
0
9
Order By: Relevance
“…These differences appear to persist throughout embryonic development (Nelissen et al, 2011;RuggGunn, 2012). Global DNA methylation is lower in the trophectoderm than in the inner cell mass of the blastocyst, and this lower methylation is retained in the extra-embryonic tissue compared with the somatic tissue (Santos et al, 2002).…”
Section: Epigenetics Placental Function and Nutritionmentioning
confidence: 99%
“…These differences appear to persist throughout embryonic development (Nelissen et al, 2011;RuggGunn, 2012). Global DNA methylation is lower in the trophectoderm than in the inner cell mass of the blastocyst, and this lower methylation is retained in the extra-embryonic tissue compared with the somatic tissue (Santos et al, 2002).…”
Section: Epigenetics Placental Function and Nutritionmentioning
confidence: 99%
“…The enzyme used to catalyze DNA methylation is DNA methyltransference (DNMTs) that included DNMT1, DNMT3a, DNMT3b and DNMT3l, in which DNMT1, as the persistent one, mainly participate in the maintenance of methylation condition, whereas DNMT3a and DNMT3b, as the de nove methyltransferences, can methylate CpG (Nelissen et al, 2011). DNA methylation has been widely used for the early diagnosis of malignant tumors such as leukemia, non-small cell lung cancer and renal cell carcinoma (Nordlund et al, 2015;Guo et al, 2015;Karami et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Because the intrauterine environment of MZ twins can differ, it is possible that intrauterine differences contribute to differences in epigenetic states. Studies investigating placental epigenetic dysregulation have identified altered DNA methylation of genes involved in placental development, including trophoblast differentiation, angiogenesis, and endocrine signaling (28). Placental epigenetic dysregulation, in particular altered DNA methylation, has been proposed as a mechanism underlying the aberrant gene expression in the pathophysiology of IUGR.…”
Section: The Discordant Mz Twin Model and Epigeneticsmentioning
confidence: 99%